2016
DOI: 10.1007/s00167-016-4346-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of demographic and pathoanatomic risk factors in recurrent patellofemoral instability

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 51 publications
0
42
0
1
Order By: Relevance
“…Thus, surgical intervention could be considered for those with ISS more than 4 points after first-time LPD. The WARPS/STAID classification system demonstrated strong relationship with ISS, providing further validation of the scoring system [34]. The WARPS subset had mean ISS of 4.4 ± 1.1 (high chances of recurrence) and STAID subset had ISS of 2.5 ± 1.5 (less chances of recurrence).…”
Section: Patellar Instability Severity Scorementioning
confidence: 75%
See 1 more Smart Citation
“…Thus, surgical intervention could be considered for those with ISS more than 4 points after first-time LPD. The WARPS/STAID classification system demonstrated strong relationship with ISS, providing further validation of the scoring system [34]. The WARPS subset had mean ISS of 4.4 ± 1.1 (high chances of recurrence) and STAID subset had ISS of 2.5 ± 1.5 (less chances of recurrence).…”
Section: Patellar Instability Severity Scorementioning
confidence: 75%
“…Hiemstra et al profiled their patients into either WARPS or STAID category, with some having mixed characteristics [34]. WARPS meant Weak, Atraumatic, Risky Anatomy, Pain and Subluxation; STAID meant Strong, Traumatic, Anatomy Normal, Instability and Dislocation.…”
Section: Combination Of Risk Factors For Recurrent Lpdmentioning
confidence: 99%
“…TD has consistently been associated with PI, and several studies 4,12,20,21,26,27,31 have identified it as either the primary or one of the strongest associated risk factors for instability or recurrent instability. Dejour et al 14 observed that in a population of patients undergoing surgical stabilization for PI, 85% had 2 radiographic signs of TD and 96% had 1 sign of TD, versus only 6% of the control group with any radiographic signs of TD.…”
Section: Discussionmentioning
confidence: 99%
“…The WARPS subtype has atraumatic onset of instability with significant risky pathoanatomy, while the STAID subtype has a traumatic onset with fewer risky anatomic features. 11,13 WARPS is an acronym that represents 5 clinical characteristics: weak, atraumatic, risky anatomy, pain, and subluxation. STAID is an acronym for clinical presentation of the following: strong, traumatic, anatomy normal, instability, and dislocation.…”
Section: Methodsmentioning
confidence: 99%